"R U Mad?": Computerized text analysis of affect in social media relates to stress and substance use among ethnic minority emerging adult males. Issue 1 (2nd January 2019) - Desrosiers, Alethea; Vine, Vera; Kershaw, Trace
ABSTRACT: Objective: This study examined the interactive role of affectivity and stress in substance use severity among ethnic minority, emerging adult males, using linguistic indicators of affect obtained through social media. Method: Participants were 119 emerging adult, ethnic minority males (ages 18–25) who provided access to their mobile phone text messaging and Facebook activity for 6-months. Computerized text analysis (LIWC2015) was used to obtain linguistic indices of positive and negative affect from texts and Facebook posts. The Perceived Stress Scale was used to measure stress, and items from the Drug Abuse Screening Test were used to measure substance use severity. Results: Generalized estimating equations showed that higher negative affect in texts was associated with greater substance use severity. Stress moderated the relationship between positive affect expressed in Facebook posts and substance use such that higher positive affect in Facebook posts was associated with less substance use at higher stress and greater substance use at lower stress. Conclusions: Findings highlight the complexities of interactions between stress and affectivity. Findings could inform development of substance use interventions for young males that employ social technologies.